What Universities Offer AI in Medicine Programs? A Guide to Top Academic Pathways in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
What Universities Offer AI in Medicine Programs? A Guide to Top Academic Pathways in Digital Health The rapid integration of Artificial Intelligence (AI...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care